Recovery of precious metals from printed circuit boards by cyanogenic bacteria: Optimization of cyanide production by statistical analysis. Issue 3 (June 2022) - Merli, Giulia; Becci, Alessandro; Amato, Alessia
Abstract: The present work was focused on mobilizing Ag from the waste printed circuit boards (WPCBs) of discarded computers by bioleaching. In this contest, bioleaching promoted by bacteria may be regarded as a potential alternative to conventional cyanidation and chemical leaching. The capacity of a cyanogenic bacteria, Pseudomonas aeruginosa ( P. aeruginosa ), for cyanide production and Ag mobilization from electronic waste was assessed. Also, in order to maximize cyanide production, the influence of the initial pH and glycine concentration was studied and optimized via central composite design of a response surface methodology (CCD-RSM). In the optimal conditions (pH 8 and 1 g/L of glycine) P. aeruginosa produced around 10 mg/L cyanide. Therefore, the bioleaching experiments were performed under the synergistic effect of glycine and cyanide through a two-step process. In the first step the bacteria were grown in the optimized conditions and in the second step, after the maximum cyanide production was reached, WPCBs were added to the growth medium and the pH was set to 9. The optimization resulted in 90% Ag mobilization. In addition, the Au bioleaching was investigated and observed with an efficiency around 20%. Considering the current availability of WPCBs on the market, the results are very promising for the development of recycling processes in the spirit of circular economy. Graphical Abstract: ga1 Highlights: A biotechnology was developed for the recovery of Ag from printed circuit boards. Cyanide was produced by P. aeruginosa at pH 8 and glycine concentration 1 g/L. Pseudomonas aeruginosa mobilized 90% of Ag by a two-step bioleaching. The combination of lab experiments and CCD-RSM optimized cyanide production.